GASTROINTESTINAL INVOLVEMENT IN SYSTEMIC SCLEROSIS: CLINICAL INSIGHTS AND EMERGING THERAPIES - Dana Bekaryssova; Gulmira Mutalipova (Central Asian Journal of Medical Hypotheses and Ethics, 2025)
Systemic sclerosis (SSc) is a chronic autoimmune disorder characterized by fibrosis of the skin and internal organs, microvascular injury, and immune system dysregulation. Among its extracutaneous manifestations, gastrointestinal (GI) involvement is one of the most common and debilitating, affecting up to 90% of patients during the disease course. GI symptoms may precede cutaneous changes and can significantly impair quality of life and prognosis. This narrative review summarizes the current understanding of the pathogenesis, clinical presentation, and management of GI involvement in SSc. The underlying mechanisms include vascular damage, immune activation, neural dysfunction, smooth muscle atrophy, and progressive fibrosis. These contribute to a wide range of motility disorders, such as esophageal dysmotility, gastroesophageal reflux disease (GERD), gastroparesis, intestinal pseudo-obstruction, and anorectal dysfunction. Additionally, small intestinal bacterial overgrowth (SIBO) and malabsorption are common complications that may lead to nutritional deficiencies and sarcopenia. In severe cases, total parenteral nutrition may become necessary. Despite its high prevalence and clinical impact, GI involvement in SSc remains frequently underrecognized and inadequately managed. Early detection, a multidisciplinary approach, and personalized treatment strategies are essential to improving patient outcomes. This review highlights the need for greater clinical awareness and continued research into targeted therapies that address the multifactorial pathophysiology of GI manifestations in systemic sclerosis.